2002
DOI: 10.1016/s0736-0266(02)00060-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte chemoattractant protein‐1 in primary cultures of rabbit intervertebral disc cells

Abstract: Macrophages are considered essential for herniated disc resorption, and chemokines may play a role in their recruitment. Here we demonstrate that intervertebral disc cells are capable of producing monocyte chemoattractant protein-1 (MCP-I), a CC chemokine that is chemotactic for macrophages. Nucleus pulposus cells and anulus fibrosus cells were harvested from intervertebral discs of healthy rabbits, and the cells were stimulated with either interleukin (IL)-lp or tumor necrosis factor (TNF)c(. Reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…In addition to these chemokines, stimulation of human AF cells with TNF-α exhibits a significant increase in the levels of CCL2, also known as monocyte chemoattractant protein-1 [96]. This is also demonstrated in rabbit AF and NP cells [97]. Taken together, these studies suggest that TNF-α acts as a key player in amplifying inflammation during disk degeneration.…”
Section: Tnf-α Amplifies the Inflammatory Responsesmentioning
confidence: 64%
“…In addition to these chemokines, stimulation of human AF cells with TNF-α exhibits a significant increase in the levels of CCL2, also known as monocyte chemoattractant protein-1 [96]. This is also demonstrated in rabbit AF and NP cells [97]. Taken together, these studies suggest that TNF-α acts as a key player in amplifying inflammation during disk degeneration.…”
Section: Tnf-α Amplifies the Inflammatory Responsesmentioning
confidence: 64%
“…Furthermore, the up-regulated production of MCP-1 in NP cells following TNF␣ stimulation has suggested that TNF␣ may also contribute to the resorption of the herniated disc through the promotion of macrophage infiltration. 42 Immunohistochemical localization studies in degenerate IVDs have shown the presence of MMPs and, thus, their potential involvement in matrix remodeling and degradation. The current study shows increased gene expression of MMP-1 and MMP-13 following exposure to levels as low as 1 ng/mL TNF␣.…”
Section: Discussionmentioning
confidence: 99%
“…41 IL-1 induced the production of collagenase, 45 cycloxygenase-2 (COX-2 46 ), prostaglandin E2, 13,47 nitric oxide, 45,44 MMP-1, 48 total 46 and active 43 MMP-3, MMP-13, 20,44 the aggrecanase, a disintegrin and metalloproteinase with t hrombo s pondin motifs-4 (ADAMTS-4), 21,44 IL-6, 46 and monocyte chemoattractant protein-1 (MCP-1). 49,50 Recently, IL-1β was shown to increase the sensitivity of IVD cells to shear stress, 51 suggesting that this cytokine is involved in the acceleration of degradation processes in IVDs subjected to biomechanical stress. Although IL-1 affects both synthetic and degradative processes, it is worth noting that, at lower concentrations, IL-1 was much more effective in inhibiting the synthesis of aggrecan than in stimulating its degradation in articular cartilage.…”
Section: Catabolic Mediators and Enzymes In Disc Degenerationmentioning
confidence: 99%